Peran Ilmu Pengetahuan Sosial dalam Pembentukan Karakter - Komang Surya Adnyana (STAHN Mpu Kuturan Singaraja, 2020)
Basically, education is an effort to develop a student’s potential optimally. Character education shapes a child's personality, in order to be better humans and better citizens, so that it is able anticipating moral degradation and have a role in the development of the younger generation. The young generation is the future hope of a country, so the young generation must has a strong character in social life. Character building is an attempt by someone to create his personal character to become a useful person for himself and surrounding. Character education must be built from an early age to make a better future. Social studies learning is really needed in shaping the character of the younger generation, where the role of social studies learning is to develop student’s knowledge, understanding, and analytical skills towards social conditions of the community. The main problem is not yet formed character of students in schools because social studies learning is still at the theory level. Though the essence of this learning is to shape students into citizens the good one which is able to apply character education in social life. Keywords: Social sciences, character